The Aftermath of Organizational Corruption: Employee Attributions and Emotional Reactions - Pelletier, Kathie L.; Bligh, Michelle C. (2008)
Employee attributions and emotional reactions to unethical behavior of top leaders in an organization recently involved in a highly publicized ethics scandal were examined. Participants (n = 76) from a large southern California government agency completed an ethical climate assessment. Secondary data analysis was performed on the written commentary to an open-ended question seeking employees’ perceptions of the ethical climate. Employees attributed the organization’s poor ethical leadership to a number of causes, including: lack of moral reasoning, breaches of trust, hypocrisy, and poor ethical behavior role modeling. Emotional reactions to corruption included cynicism, optimism, pessimism, paranoia and fear, and were targeted at top leaders, organizational practices (i.e., the old boy network, nepotism, and cronyism) and ethics interventions. Implications for leadership training and other organizational ethics interventions are discussed.
Keywords: Unethical Behavior; ethics scandal; Ethical decision making; employee reactions; Corruption